Comparative Outcomes of Robotic-Assisted And Fluoroscopy-Guided Pedicle Screw Placement In Lumbar Degenerative Disease: A Systematic Review And Meta Analysis - Ahmad Zidane; Oktavio Jalu Kuncoro Jati (CV. Inara, 2026)
Introduction: Pedicle screw fixation is a cornerstone of lumbar spine surgery, but fluoroscopy-guided placement is associated with screw malposition, cortical breach, facet joint violation, and radiation exposure. Robotic-assisted techniques have been developed to improve trajectory planning, placement accuracy, and procedural safety. This systematic review and meta-analysis compared robotic-assisted and fluoroscopy-guided pedicle screw placement in spinal surgery, with emphasis on accuracy and perioperative outcomes. Materials/Methods: A systematic search of PubMed and ScienceDirect was conducted for studies published between 2022 and 2025 using keywords related to fluoroscopy, robotic assistance, spine, and pedicle screws. Retrospective cohort and retrospective comparative studies evaluating robotic-assisted versus fluoroscopy-guided pedicle screw insertion were included. Outcomes included screw placement accuracy, intraoperative blood loss, radiation exposure, complications, and hospital-related outcomes. Meta-analysis was performed using Review Manager 5.3. Odds ratios were used for dichotomous outcomes, while mean differences or standardized mean differences were used for continuous outcomes. Results: Five retrospective studies involving 710 patients and 4,434 pedicle screws were included. Robotic-assisted placement demonstrated significantly higher screw accuracy than fluoroscopy-guided placement, involving 1,937 robotic screws and 2,497 fluoroscopy-guided screws. The pooled analysis showed that robotic assistance was associated with greater odds of accurate screw placement (OR 2.73; 95% CI 1.50–4.97; p = 0.001), although heterogeneity was moderate to substantial (I² = 66%). Blood loss was lower in the robotic group by 73.06 mL, but this difference was not statistically significant (95% CI −225.18 to 79.06; p = 0.35; I² = 98%). Radiation exposure was significantly reduced with robotic assistance, showing a large effect size favoring robotics (SMD −1.63; 95% CI −2.55 to −0.71; p = 0.0005), despite substantial heterogeneity (I² = 93%). Conclusion: Robotic-assisted pedicle screw placement provides superior screw accuracy and significantly reduces radiation exposure compared with fluoroscopy-guided techniques. However, evidence for reduced blood loss remains inconclusive. Further prospective studies are required to confirm clinical benefits and long-term outcomes